Pelong Ya Ka - Mofokeng, ...,Mahase, ... (Wits University Press, 2021)
Pelong ya ka is a volume of Sesotho essays and stories on personal themes, first published in 1962. The author, an expert on African folklore, was also regarded as a gifted exponent Southern Sesotho. The pieces in this collection are narrative in style and largely autobiographical.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books